Microservices Communication in .NET Using gRPC : A practical guide for .NET developers to build efficient communication mechanism for distributed apps /: A practical guide for .NET developers to build efficient communication mechanism for distributed apps. (2022) - Sazanavets, Fiodar
No abstract available